Systematic review: Xenopus laevis as a model for ophthalmic development and disease research - Li, Qiaoyu; Feng, Yun; Zhu, Xuechen (Frontiers in Medicine, 2025)
Model organisms have played a pivotal role in ophthalmic research, providing essential platforms to investigate eye development, regeneration mechanisms, and disease pathology. Recent advancements in gene editing technologies and experimental methodologies have enabled the successful simulation of various human eye diseases, including glaucoma, retinal degeneration, and corneal disorders in model systems. These models have significantly advanced the understanding of the molecular and cellular mechanisms underlying ocular diseases and facilitated the screening and validation of potential therapeutic agents. Xenopus laevis (X. laevis) has emerged as an ideal system for developmental biology research due to its rapid embryonic development, transparent embryos, and ease of observation and manipulation. Its fully sequenced genome allows precise genetic modifications, including gene knockout, knock-in, and expression regulation studies. In ophthalmic research, X. laevis is widely used for studying eye development, disease modeling, and ocular structure. Its accessible embryonic stages and well-characterized eye development make it a valuable model for retinal disease investigations. This review systematically summarizes the applications, construction methods, and research significance of X. laevis models in eye development, disease modeling, and drug screening. It provides an in-depth perspective on the utility of X. laevis in foundational ophthalmic research, offering insights to guide future studies.